Pengendalian Persediaan Bahan Baku Penolong Menggunakan Metode Economic Order Quantity di Industri Makanan Olahan - Mufti, Wahyu Fitrianda; Zulhamidi; Rusmin, Salman Alfarissi; Musdirwan (Politeknik ATI Padang, 2022)
CV. XYZ is a company engaged in food processing, it processes meat as the main raw material. Beef rollade is one of the products produced by CV. XYZ using